2015
DOI: 10.1128/jvi.03085-14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus-Mediated Enhancement of MicroRNA miR-373 Impairs the JAK/STAT Signaling Pathway

Abstract: Hepatitis C virus (HCV) is a serious global health problem and establishes chronic infection in a significant number of infected humans worldwide. Interferon (IFN) and IFN-stimulated genes (ISGs) are amplified during HCV infection but fail to eliminate virus from the liver in a large number of infected patients, and the mechanism is not fully understood. MicroRNAs (miRNAs) have been implicated in the control of many biological processes, including IFN signaling. To gain more insights into the role of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 31 publications
1
67
1
Order By: Relevance
“…In addition, previous studies have shown miR-373 could inhibit the type I IFN receptor signaling pathway by targeting IRF9 (36), and our results also showed that IFNAR1 and IFNAR2 were potential target genes of miR-373, which indicated that miR-373 also targets IFNAR1 and IFNAR2 for its inhibiting the type I IFN receptor signaling pathway (Fig. 4).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In addition, previous studies have shown miR-373 could inhibit the type I IFN receptor signaling pathway by targeting IRF9 (36), and our results also showed that IFNAR1 and IFNAR2 were potential target genes of miR-373, which indicated that miR-373 also targets IFNAR1 and IFNAR2 for its inhibiting the type I IFN receptor signaling pathway (Fig. 4).…”
Section: Discussionsupporting
confidence: 58%
“…miR-373 could act as an oncogene or a tumor suppressor in different cancers (55). There are also a few reports that miR-373 could enhance the replication of HBV (35) and HCV (36). Here, we found evidence that miR-373 facilitated the replication of PRRSV, and we also investigated the mechanisms.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, MLV suppresses the activation of ISG15 and ISG56 induced by IFNs in MARC-145 cells, implying that other mechanisms might contribute to the impairment of IFN-I signaling during PRRSV infection (43). Cellular miRNAs were shown to be used by viruses to evade IFN-I-mediated antiviral responses in host cells (18,21,44,45). However, whether miRNAs participate in PRRSV-mediated evasion of IFN-I-mediated antiviral responses remains elusive.…”
Section: Mir-30c Correlates With Prrsv Infection In Vivomentioning
confidence: 99%
“…They are increased by infection to target key viral sensors, mediators of the IFN activation and signaling or antiviral genes. Examples of this include targeting of TLR3 by miR-758, targeting of factors involved in the TLR signaling such as MyD88 and IRAK1 by miR-21, targeting of JAK1 and IRF9 by miR-373(Mukherjee et al, 2015) or targeting of the antiviral factor IFITM1 by miR-130a(Bhanja Chowdhury et al, 2012).…”
mentioning
confidence: 99%